Increasing Seaweed Consumption in the Netherlands and Portugal and the Consequences for the Intake of Iodine, Sodium, and Exposure to Chemical Contaminants: A Risk-Benefit Study - Vellinga, Reina Elisabeth; Sam, Matthijs; Verhagen, Hans; Jakobsen, Lea Sletting; Ravn-Haren, Gitte; Sugimoto, Minami; Torres, Duarte; Katagiri, Ryoko; Thu, Beate Julie; Granby, Kit; Hoekstra, Jeljer; Temme, Elisabeth Helena Maria (Frontiers in Nutrition, 2022)
Background: Seaweed has high potential for nourishing the future planet. However, besides beneficial it also contains adverse components; this poses the question whether consumption of seaweed foods overall contributes beneficially or detrimentally to human health, and hence if their consumption should be promoted or restricted. Methods: This study evaluated the impact of substituting regular foods with seaweed foods in the diet, both in terms of nutritional quality (via Iodine and Sodium) and food safety (via Arsenic, Cadmium, Lead and Mercury). Food consumption data from the Netherlands and Portugal (adults aged >18 y) were used, in which 10% of the amounts of pasta, bacon and lettuce consumed were replaced by seaweed-derived products made from kelp (Saccharina latissima). Using Monte Carlo Risk Assessment software (MCRA), long-term nutrient intake and exposure to contaminants were assessed. The results obtained for the Netherlands and Portugal were compared with data from Japan, a country that has a high natural consumption of seaweed. Results: This low-tier risk-benefit study reveals that an increased seaweed consumption (as assessed by the 10% replacement with seaweed products) has no consequences in terms of intake of Sodium, and exposure to Cadmium, Lead and Mercury and the associated (absence of) adverse health aspects. The alternative scenario almost doubled the mean Iodine intake in the Netherlands (to 300 µg/day) and Portugal (to 208 µg/day) and increased the average exposure to Arsenic levels in the Netherlands (to 1.02 µg/kg bw/day) and Portugal (to 1.67 µg/kg bw/day). Conclusion: The intake of Iodine and exposure to Arsenic in the Netherland and Portugal were certainly higher due to the modelled increase of seaweed foods. If seaweed consumption increases close to the 10% substitution, the public health consequences thereof may trigger further research.